Advances in distribution theory, order statistics, and inference - International Conference on Distribution Theory, Order Statistics, and Inference ( 2004 : Universidad de Cantabria); Balakrishnan, N., 1956-; Castillo, Enrique, 1946-; Sarabia, Jose-Maria (New York, NY :, 2006)
41